Polyphonic Social Voices: A Deconstructive Reading of Facebook Threads in the Context of Social Studies Education - Riza Mae Riel; Marlon Salvador (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aimed to critically analyze Facebook comments on Miss Universe pageants to uncover recurring social issues, explore how users express desires for dominant ideals, and examine how binary oppositions are constructed and challenged within online discourse, particularly in relation to representation, identity, and cultural perception. Methodology: This study employed qualitative content analysis using NVivo software for systematic coding and thematic analysis. A total of 125 public Facebook threads from 2015 to 2019 were reviewed. Data were extracted from unsolicited user comments. The analysis was guided by Derrida’s deconstructive framework and implemented through structured thematic coding procedures. Main Findings: Findings revealed 13 dominant social issues including marginalization, colorism, phenotype bias, gender discrimination, and language elitism. Netizens expressed desires related to national identity, authenticity, and physical standards. Twenty-eight binary oppositions, such as fake/real and white/black, were deconstructed to show coexistence and the possibility of inclusive meaning-making in social spaces. Novelty/Originality of this study: This study uniquely integrates Derrida’s deconstruction with social media discourse to examine digital identity narratives. It introduces a framework for educators and researchers to analyze online texts critically, promoting inclusive digital literacy. It advances social studies education by bridging theory, online behavior, and sociocultural critique in a digital context.